Theoretical study the electronic, elastic properties and thermodynamics properties of ternary phosphide SrPt6P2. (July 2017) - Tian, Wenyan; Cai, Jianghui; Chen, Haichuan
Abstract: The structural, electronic, elastic properties of superconductivity SrPt6 P2 have been investigated and analyzed using generalized gradient approximation within the density functional theory. The optimized lattice constant is in well agreement with the experimental data. The total density of states (DOS) results demonstrates that SrPt6 P2 is metallic in character, and the Fermi level is mainly the contribution of 5d orbitals of Pt and with small contributions from P- p and Sr- d states. The elastic constants, bulk modulus, Young's modulus and shear modulus are also successfully obtained. The calculated elastic constants meet the mechanical stability criteria. The B/G ratio, Poission's ratio and Cauchy pressure indicated that it possesses ductile. The Vickers hardness is 7.49 GPa, suggesting that it is a soft material. Though the quasi-harmonic Debye model, the thermodynamics properties of SrPt6 P2 have been obtained. The results show the C v, C p and α is about 863.5 J/mol K, 895.6 J/mol K and 4.0 5 ×10 5 K −1 at 0 GPa and 300 K, respectively. The Debye temperature is 273.7 K, melting temperature is 2271±300 K and the minimum thermal conductivities k min is 0.495 W m −1 K −1 . It has also been shown that the C v, C p and α decrease with increasing pressure at given temperature while increase with increasing temperature at given pressure. Finally, the superconducting parameters are evaluated by the McMillan equation. Highlights: The mechanical of SrPt6 P2 have been investigated. The total density of states results demonstrates that SrPt6 P2 is metallic. SrPt6 P2 hold a ductile behavior and the Vickers hardness is 7.49 GPa. The C v, C p and α is about 863.5 J/mol K, 895.6 J/mol K and 4.05×10 5 K −1 at 300 K and 0 GPa, respectively. The Debye temperature is 273.7 K, and melting temperature is 2271±300 K.